Microplastics in freshwater systems: A review on occurrence, environmental effects, and methods for microplastics detection - Li, Jingyi; Liu, Huihui; Paul Chen, J. (Water research (Oxford), 2018)
The continuous increase in synthetic plastic production and poor management in plastic waste have led to a tremendous increase in the dumping into our aqueous environment. Consequently, microplastics commonly defined as sizes less than 5 mm are produced and stay in both seawater and freshwater environment. The presence of microplastics as a new type of emerging contaminant has become a great issue of concerns from public and government authorities. The sources of microplastics to freshwater systems are many with the largest portion from wastewater treatment plants. The abundance of microplastics varies with the location, from above 1 million pieces per cubic meter to less than 1 piece in 100 cubic meters. Microplastics can cause several harmful physical effects on humans and living organisms through such mechanisms as entanglement and ingestion. The microplastics can act as carriers of various toxins such as additives from industrial production processes and persistent contaminants by the sorption in waters. Those toxins may cause great health problems to humans. A few studies on the fishes demonstrated that the microplastics and the associated toxins are bio-accumulated and cause such problems as intestinal damage and change in metabolic profiles. In studies of microplastics, fresh water is first sampled by the nets with typical mesh size of 330 μm for collection of microplastics. After the volume reducing process, the samples will then go through the purification process including density separation by such inorganic salts as sodium chloride and digestion process by oxidizing agents or enzymes. The sequence of these two processes (namely purification and digestion) is dependent on the sample type. The purified samples can be studied by several analytical methods. The commonly used methods for the qualification studies are FTIR spectroscopy, Raman spectroscopy, pyrolysis-GC/MS, and liquid chromatography. A tagging method can be used in the quantification study. Our literature study finds that there is still no universal accepted quantification and qualification tools of microplastics in fresh waters. More work is anticipated so as to obtain accurate information on microplastics in freshwater, which can then be used for the better assessment of the environmental risk. •Microplastics exhibit high abundance in freshwater systems.•The knowledge about health impacts of freshwater microplastics is limited.•A summary of current microplastics research methodology is included.•Combination of appropriate analytical approaches should be adopted to assess microplastics in freshwaters.